Evaluations Of 3m Fluorad™ Fc-gold On Gold Extraction From Production Heap Leaching At Daisy Gold Mine (Glamis Gold) - Tom Barrett; Shawn Orser; Mike Sierakowski; Jennifer Waddell (Society for Mining, Metallurgy & Exploration, 2000)
Production evaluations were conducted at Daisy Gold Mine (Glamis Gold, formerly Rayrock), between August, 1997 and August, 1998 to quantify the effect of 3M fluorochemical surfactants (fluorosurfactants) on extraction kinetics and gold recovery in gold heap leach mining operations. Ore was treated at a level of 7-10 grams surfactant per ton of ore using 3M Pluorad TM Leach Mining Additive PC-GOLD. Kinetics and gold recovery were determined by solution assay for each of the tests. Both tests indicated improved kinetics, and data from Test 2 was used for determination of a quantitative increase in gold recovery resulting from PC-GOLD addition. A discussion of test results including methods used to determine gold recovery is provided.